Growth and trade horizons for Asia: Long term forecasts for regional integration - David Roland-Holst; Jean-Pierre Verbiest; Fan Zhai (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
Economic emergence of the People's Republic of China (PRC) and India has fundamentally altered the economic landscape of Asia and its relation to the global economy. Using the new dynamic global model, we present forecasts for Asian expansion over 2025. These baseline growth forecasts elucidate shifting patterns of regional specialization and their consequences for growth and structural change in the Asian economies. The central role of trade is examined through analysis of a variety of hypothetical global and regional trade agreements. Our results indicate that trade within the Asian region is far from reaching its potential, and policies that facilitate integration and more efficient regional trade can accelerate growth, especially for lower-income Asia. A deeper and more inclusive Asian free trade area can achieve for its members large benefits. As an emerging growth bridge between the PRC and India, ASEAN economies have the most to gain from Asian economic integration.
Keywords: F02; N15; O53; 330; globalization; integration; Asia; Außenwirtschaft; Wirtschaftswachstum; Wirtschaftsintegration; Prognose; Asien